Analisis Efektivitas Platform Instagram Dalam Strategi Promosi Senja Coffee And Kitchen Pasca Pandemi Covid 19 Di Jember - Ramadani, Tommy Anugrah; Syahrinullah, Syahrinullah (LPPM Universitas Muhammadiyah Mamuju, 2023)
The purpose of this research is to examine promotion strategies through Instagram social media by Senja Coffee and Kitchen in increasing post-pandemic sales. This study uses a descriptive qualitative approach involving observation and in-depth interviews. A total of 10 respondents were involved in this study, namely parties related to Senja Coffee and Kitchen. The data obtained from this research provides valuable insight into the promotion strategy that has been implemented by Senja Coffee and Kitchen, including the promotional stages used to maximize marketing. The results of the study show that the promotion strategy for Senja Coffee and Kitchen through social media Instagram is very effective in increasing visibility, attractiveness and sales at Senja Coffee and Kitchen in Jember. The implications of this research emphasize the importance of utilizing social media, especially Instagram, as an effective means of promotion for coffee shop businesses. This research provides valuable insights for the coffee shop industry in developing effective promotional strategies through social media.